2004
DOI: 10.1002/ejic.200300271
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and X‐ray Crystal Structures of Cobalt and Copper Complexes of 1,3‐Bis(benzotriazolyl)propanes

Abstract: Two propylene-bridged bis-benzotriazole ligands, 1 and 2, were used to obtain three novel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…The radical-scavenging (RS) activities of L and its two complexes were tested using the pyrogallol autoxidation method [18][19][20]. For the control experiment: Tris-HCl buffer (5 mL, pH = 8.2) was mixed with double distilled water (5 mL), and the mixture was kept at 25.0 ± 0.2°C for 20 min.…”
Section: Measurement Of Radical-scavenging Activitiesmentioning
confidence: 99%
“…The radical-scavenging (RS) activities of L and its two complexes were tested using the pyrogallol autoxidation method [18][19][20]. For the control experiment: Tris-HCl buffer (5 mL, pH = 8.2) was mixed with double distilled water (5 mL), and the mixture was kept at 25.0 ± 0.2°C for 20 min.…”
Section: Measurement Of Radical-scavenging Activitiesmentioning
confidence: 99%
“…For the isomeric chain structure, see Borsting & Steel (2004). For the synthesis of the ligand, see: Xie et al (2000).…”
Section: Related Literaturementioning
confidence: 99%
“…We have long been involved in the synthesis and study of metal complexes of new heterocyclic ligands (Steel, 2005). In particular, we have been interested in the design of ligands incorporating less commonly studied heterocyclic ring systems, such as tetrazoles (Downard et al, 1995), 1,2-benzisoxazoles (Richardson & Steel, 2000a), furoxans (Richardson & Steel, 2000b), 1,2,5-oxadiazoles and 1,2,5-thiadiazoles (Richardson & Steel, 2001;, 1,2,3thiadiazoles (and selenadiazoles) , pyridazines (Sumby & Steel, 2003), 1,4,2,5-dioxadiazines (Richardson & Steel, 2003a), benzotriazoles (Richardson & Steel, 2003b;Borsting & Steel, 2004), and thiazolo [5,4d]thiazoles (Zampese et al, 2004). 2,5-Diphenyl-1,3,4-thiadiazole has been known for more than half a century (Chabrier et al, 1949), but the first metal complex containing this ligand was reported only recently (Franski & Gierczyk, 2005).…”
Section: Commentmentioning
confidence: 99%